A comparison of absolute, ratio and allometric scaling methods for normalizing strength in elite American football players - Jacobson, B. H.; Thompson, B. J.; Conchola, E. C.; Glass, R. (Journal of Athletic Enhancement, 2013)
Division I football players exemplify the greatest range in body mass of any modern team sport. Body mass may differ by over 80 kg between the various positions. Absolute muscular strength is typically greater in larger individuals, but such data does not allow for accurate comparisons. Therefore, in order to compare the performance indices of individual groups allometric rather than ratio scaling has been suggested. The purpose of this study was to compare absolute strength, normalized ratio and allometrically scaled data among players of different size. Following IRB approval, data were accessed on NCAA Division I football players over a six-year period at a mid-western university. Of the 606 cases accessed, the following characteristics were recorded: mean ± SD: age=20.1 ± 1.3, mass=107.38 ± 20.30 kg, height=186.76 ± 8.6 cm. With the exception of kickers, participants consisted of all offensive and defensive football players. Players were categorized into seven weight and seven height groups. Data on 1RM bench press and squat were recorded as absolute and subsequently ratio and allometrically scaled. Based on recommendations, the bench press and squat were scaled allometrically using m2/3 and m-1/3 for the bench press and squat respectively. Results of repeated measures ANOVAs yielded significant (p<0.05) and a near linear pattern of absolute strength by body mass, a significantly greater strength ratio for lighter mass than heavier mass, and no significant difference among the groups following allometric scaling. Results suggest that it may be possible to determine if an athlete falls within an acceptable range of the established standards derived from allometric scaling. Also, if an athlete falls outside by, say one standard deviation, he may demonstrate below acceptable performance and/or be more injury susceptible which should initiate a need for additional work.